2013
DOI: 10.3390/ma6010359
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Characterization of Lignin Polymer by Solution-State Nuclear Magnetic Resonance (NMR) Methodology

Abstract: The demand for efficient utilization of biomass induces a detailed analysis of the fundamental chemical structures of biomass, especially the complex structures of lignin polymers, which have long been recognized for their negative impact on biorefinery. Traditionally, it has been attempted to reveal the complicated and heterogeneous structure of lignin by a series of chemical analyses, such as thioacidolysis (TA), nitrobenzene oxidation (NBO), and derivatization followed by reductive cleavage (DFRC). Recent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
445
0
6

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 640 publications
(468 citation statements)
references
References 82 publications
17
445
0
6
Order By: Relevance
“…Recent structural characterization of cell walls from monocot species using NMR showed that the flavone tricin [5,7-dihydroxy-2-(4-hydroxy-3,5-dimethoxyphenyl)-4H-chromen-4-one] is part of the native lignin polymer in wheat (Triticum aestivum; del Río et al, 2012;Zeng et al, 2013), coconut (Cocos nucifera) coir (Rencoret et al, 2013), bamboo (Phyllostachys pubescens; Wen et al, 2013), maize (Zea mays; Lan et al, 2015), and sugarcane (Saccharum officinarum; del . Tricin is the first flavonoid that is recognized to be an authentic monomer involved in lignification (del Río et al, 2012;Lan et al, 2015).…”
mentioning
confidence: 99%
“…Recent structural characterization of cell walls from monocot species using NMR showed that the flavone tricin [5,7-dihydroxy-2-(4-hydroxy-3,5-dimethoxyphenyl)-4H-chromen-4-one] is part of the native lignin polymer in wheat (Triticum aestivum; del Río et al, 2012;Zeng et al, 2013), coconut (Cocos nucifera) coir (Rencoret et al, 2013), bamboo (Phyllostachys pubescens; Wen et al, 2013), maize (Zea mays; Lan et al, 2015), and sugarcane (Saccharum officinarum; del . Tricin is the first flavonoid that is recognized to be an authentic monomer involved in lignification (del Río et al, 2012;Lan et al, 2015).…”
mentioning
confidence: 99%
“…13 Ce xperiments that suffered from insufficient resolution to distinguish subtle structural details, and are now widely employed for the investigation of lignin composition and structure.T he interested reader is referred to thorough recent review articles on the methodology, potential and limitations of NMR spectroscopy for the characterisation of lignin, even without requiring its isolation from the cell wall. [33,34] HSQC experiments have been instrumental in the identification and (approximate) estimation of the relative abundance of bonding motifs of the types A, B, C, D and F (Scheme 5) and other structural elements that may occur both in untreated native lignins (e.g., spirodienone moieties,derived from b-1 coupling of amonolignol with apreformed b-ether unit), [164] and residual linkages in the depolymerised material. [165] Expansive literature,a nd two book chapters, [31,166] describe its application to deduce the changes in normal units and to elucidate and validate new products in the many transgenics.…”
Section: Structural Features Of Native Ligninsmentioning
confidence: 99%
“…Actually, lignin has complicated NMR signals since it has many groups. However, the dominant NMR signals of lignin are assigned to protons in C-H of methoxyl groups that have chemical shift 3.70-3.81 ppm [23,24]. Even though there were impurities, recycled ionic liquid was still good enough to conduct pretreatment of biomass.…”
Section: Characterization Of the Ionic Liquid [Mmim][dmp]mentioning
confidence: 99%